Modeling Private Sector Development in the People's Republic of China - Toshiki Kanamori; Zhijun Zhao (Asian Development Bank Institute (ADBI), 2005)
In this paper, a simplified mathematical model based on the behavioral pattern of firms in the PRC is used to discuss the impact of marketization and privatization on private sector development. The model demonstrates that private enterprises, SOEs, and other entities undergoing reform in the PRC are entities with multiple objectives. This pattern of behavior leads to firms that tend to use more capital and labor to produce more output compared with pure profit-maximizing firms, but which earn fewer profits or even register losses. The impacts of firms' non-profit objectives and the “costs of entry” on the size and number of firms are also discussed. The problem of matching between managerial ability and firm size is introduced to explain why gradual reform in PRC has succeeded, whereas the “Big Bang” in Russia failed.
hdl:11540/4167
Keywords: 330; Systemtransformation; Privatwirtschaft; Privatisierung; China